Handling qualities of high aspect ratio wing aircraft. - Portapas, Vilius (Cranfield University, 2018)
To reduce the environmental impact of the aviation industry aircraft designers invest much effort to develop new and improve existing technologies to create new aircraft configurations. New high aspect ratio wings allow to improve aerodynamic efficiency while reducing aircraft weight through the use of new lightweight materials. However, their slenderness tends to introduce significant interaction between flight dynamics and aeroelastics. These interactions need to be identified in order to allow future pilots to anticipate behaviour of those aircraft. The literature review revealed a gap in the knowledge of flying and handling qualities (HQs) of large transport highly flexible wing aircraft. Hence, this thesis presents a comparison between rigid and flexible aircraft configurations carried out by the means of the pilot-in-the-loop simulations of flight test manoeuvres. Firstly, the analysis of the extended equations of motion, which consider the structural flexibility, revealed significant flexibility impact on the lateral/directional dynamics of the aircraft. Then, the equations were integrated into the Simulation Framework for Flexible Aircraft (SFFA) that was developed by integrating the aeroservoelastic model CA² LM with the engineering flight simulator EFS500. The simulation campaign was performed using the SFFA for the HARTEN aircraft model, which exhibited an unusually aft neutra point position. The results of the simulation campaign revealed minor differences in the longitudinal dynamics between the rigid and flexible aircraft. However, the lateral/directional dynamics showed significant differences, especially in the change of the Dutch roll shape from horizontal to vertical and the spiral mode from unstable to neutrally stable. It also highlighted the ‘wing rocking’ phenomenon and the ‘wing ratcheting’ significantly decreased roll performance. Finally, a new slalom task proved its applicability to efficiently assess HQs and revealed a degradation of HQs for the flexible aircraft configuration. The SFFA was also assessed and limiting hardware issues were indicated to support the comparison of aircraft HQs. For the future it is recommended to identify a set of dynamic parameters that would allow to highlight deficiencies of flexible aircraft and to improve the SFFA allowing pilots to fully concentrate on the task.
Keywords: Aeroservoelasticity; aircraft dynamics; flexible aircraft; flight dynamics; flying qualities; handling qualities; pilot-in-the-loop simulation